The Trajectory of Electoral Democracy: Legality, Systems, and the Development of Indonesian Election Outcomes - Muhammad Kevin Mulyawarman; Muhammad Fasya Haifa; Adi Gunawan GN; Zulfiqri; Elviandri (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2026)
Elections are a fundamental tool in a democratic system that serve to realize the rights of the people. This paper aims to examine the background and evolution of elections in Indonesia, including the legal basis, electoral system, organizing institutions, and election results over time. The approach used is a normative juridical approach with descriptive analysis of legislation and related scientific literature. The results of the discussion indicate that elections in Indonesia have experienced significant progress, starting from the 1955 election, which was considered the most democratic, then declining during the New Order era to become a tool for legitimizing power, until re-emerging as a competitive multiparty system after the 1998 reforms. Institutionally, the General Elections Commission (KPU), Elections Supervisory Agency (Bawaslu), and Elections Executive Board (DKPP) were designed as independent organizers, but still face integrity and capacity challenges. The implementation of an open proportional system and simultaneous elections brought democratic progress as well as new issues such as increased money politics and high technical burdens for election officials in the field. This paper recommends the need to strengthen election organizing institutions, reform the election system with a humanitarian perspective, and improve public political education to realize more transparent, accountable, and high-quality elections.